Analisis Hubungan Antara Minat Kaligrafi Dengan Keterampilan Menulis Arab Mahasiswa Pendidikan Bahasa Arab UIN Sumatera Utara - Habibah Khairani; Mawaddah Mumtazah Nasution; Regina Valda Garzita; Tria Wulandari; Sahkholid Nasution (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2024)
Discussions about calligraphy as an art in an Islamic context have eternal appeal, highlighting the beauty and depth of meaning in every stroke of the letters, especially in the Al Quran. The art of calligraphy is not only a visual art but also an important bridge to understanding and learning Arabic. Arabic has a crucial role in Islamic education, not only as a means of religious communication but also as a broad window into Islamic history and literature. In this context, Arabic Language Education students at UIN North Sumatra found an interest in calligraphy as an enrichment in learning, opening up space for cultural and artistic exploration related to the Arabic language. This research adopted a qualitative descriptive method to explore the relationship between interest in calligraphy and Arabic writing skills among Arabic Language Education students at UIN North Sumatra. Through interviews and literature analysis, this research highlights the role of interest in calligraphy in improving Arabic writing skills. The research results show that interest in calligraphy significantly influences students' proficiency and talent in writing Arabic. Students with both interests and talents tend to have better support, while those with only interests need more support. This research highlights the importance of interest in calligraphy in improving Arabic writing skills, illustrating the role of supporting factors and the difference between talent and interest.